The Influence of Nutrition on Intestinal Permeability and the Microbiome in Health and Disease - Inczefi, Orsolya; Bacsur, Péter; Resál, Tamás; Keresztes, Csilla; Molnár, Tamás (Frontiers in Nutrition, 2022)
The leakage of the intestinal barrier and the disruption of the gut microbiome are increasingly recognized as key factors in different pathophysiological conditions, such as IBS, IBD, chronic liver diseases, obesity, diabetes mellitus, cancers, and neuropsychiatric disorders. In this paper, the mechanisms leading to dysbiosis and “leaky gut” are reviewed, and a short summary about the current knowledge regarding to different diseases is provided. The simplest way to restore intestinal permeability and the microbiota could be ideal nutrition. Further therapeutic options are also available, such as the administration of probiotics or postbiotics, or fecal microbiota transplantation.